1990
DOI: 10.1056/nejm199009063231003
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer and Exposure to Tobacco Smoke in the Household

Abstract: The possibility of recall bias and other methodologic problems may influence the results of case-control studies of environmental tobacco smoke. Nonetheless, our findings regarding exposure during early life suggest that approximately 17 percent of lung cancers among nonsmokers can be attributed to high levels of exposure to cigarette smoke during childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
2
10

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(117 citation statements)
references
References 17 publications
4
101
2
10
Order By: Relevance
“…Results have been mixed as to whether or not it is a risk factor for lung cancer in nonsmokers. Some studies report a positive association with spousal exposure [32][33][34], while others do not [35,36]. Some studies have found a positive association with childhood exposure [34,35], while others have not [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Results have been mixed as to whether or not it is a risk factor for lung cancer in nonsmokers. Some studies report a positive association with spousal exposure [32][33][34], while others do not [35,36]. Some studies have found a positive association with childhood exposure [34,35], while others have not [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence (19,22,29,30) suggests that exposure to SHS in childhood increases the risk of lung cancer in adulthood. With the decline of adult smoking in public and work places in the United States and Europe but still very prevalent in other regions around the world, SHS exposure and associated risks are still a major source of uncontrolled exposure in younger individuals, especially in children without the ability to negotiate a smoke free environment at home, work or leisure.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have focused on paternal and maternal smoking during pregnancy and the effect on childhood illnesses and cancers in general or more recently the risk of lung cancer for non-smoking women exposed to tobacco smoke during childhood (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Very few studies (19,22,29,30) have focused on the effect of the period of exposure relevant for lung cancer development while also assessing the significance of lifetime exposure by location.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer deaths from passive cigarette smoke exposure account for approximately a quarter of lung cancers seen in never smokers (Janerich et al 1990). The RR of lung cancer in married never smokers varies up to 3.4, increasing with increased spousal cigarette consumption (USDHHS 1986;Fontham et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…A heavy smoker may accumulate an alpha-radiation dose as high as 1 Gy, mostly from 210 Po, to bronchial bifurcations (Martell 1975). The interaction of radiation and smoking exhibits a sub-multiplicative or multiplicative relationship in the induction of lung cancer (Martell 1975;Gray et al 1986;Janerich et al 1990;Monchaux et al 1994;Thomas et al 1994;Barros-Dios et al 2002;Gilbert et al 2003;Pierce et al 2003;Wang et al 2005). Cigarette smoking so confounds studies of lung cancer formation in irradiated populations that it is difficult to determine if ionizing radiation even exerts a significant effect on lung cancer formation in smokers with a RR < 1.5-2.0 (Doll 1992;Schull and Weiss 1992), and little is known about the interaction of smoking and radiation on non-respiratory tract cancers.…”
Section: Interaction Of Radiation and Smokingmentioning
confidence: 99%